Sequential role of RAD51 paralog complexes in replication fork remodeling and restart - Berti, Matteo; Teloni, Federico; Mijic, Sofija; Ursich, Sebastian; Fuchs, Jevgenij; Palumbieri, Maria Dilia; Krietsch, Jana; Schmid, Jonas A.; Garcin, Edwige B.; Gon, Stéphanie; Modesti, Mauro; Altmeyer, Matthias; et al. (Nature communications, 2020)
Homologous recombination (HR) factors were recently implicated in DNA replication fork remodeling and protection. While maintaining genome stability, HR-mediated fork remodeling promotes cancer chemoresistance, by as-yet elusive mechanisms. Five HR cofactors – the RAD51 paralogs RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3 – recently emerged as crucial tumor suppressors. Albeit extensively characterized in DNA repair, their role in replication has not been addressed systematically. Here, we identify all RAD51 paralogs while screening for modulators of RAD51 recombinase upon replication stress. Single-molecule analysis of fork progression and architecture in isogenic cellular systems shows that the BCDX2 subcomplex restrains fork progression upon stress, promoting fork reversal. Accordingly, BCDX2 primes unscheduled degradation of reversed forks in BRCA2-defective cells, boosting genomic instability. Conversely, the CX3 subcomplex is dispensable for fork reversal, but mediates efficient restart of reversed forks. We propose that RAD51 paralogs sequentially orchestrate clinically relevant transactions at replication forks, cooperatively promoting fork remodeling and restart. Replication stress has been associated with transient remodelling of replication intermediates into reversed forks, followed by efficient fork restart. Here the authors systematically analyse the role of RAD51 paralogs in these transactions, providing insights on the mechanistic role of different complexes of these proteins.